Efficient strategy for interchangeable roles in a green and sustainable redox catalytic system: IL/PdII-decorated SBA-15 as a mesoporous nanocatalyst. (26th March 2021) - Sadeghi, Samira; Karimi, Meghdad; Radfar, Iman; Gavinehroudi, Reza Ghahremani; Saberi, Dariush; Heydari, Akbar
Abstract : Green synthesis of catalyst for the aerobic oxidation of alcohols using air as a green oxidant, and efficient and straightforward synthesis method for amine formation using formic acid as a green reductant. Abstract : Time and again, SBA-15-based composites as mesoporous materials and the incorporation of transition metals in them have been attracting dramatic attention in the field of catalysis due to their remarkable features. In this paper, the activity of SBA-15 supported ionic liquid–Pd(ii ) has been investigated in the catalytic transfer hydrogenation of nitroarenes with formic acid as a hydrogen donor at room temperature in water medium, and the oxidation of benzyl alcohols to benzaldehyde derivatives under atmospheric oxygen at high temperature. This novel nanocatalyst was characterized by FT-IR, SA-XRD, BET, BJH, TGA, FE-SEM, TEM, and ICP as the most commonplace techniques for analyzing its characteristics to be revealed as truth. Furthermore, the EDX analysis illustrates the grafting of the ionic liquid–Pd(ii ) into SBA-15. The catalyst showed high stability under reaction conditions, and can be recovered and reused for at least 15 and 6 reaction runs in oxidation and reduction reactions, respectively.